Recent progress of tapered optical fiber for biosensing applications - Haroon, Hazura; Anbalagan, Thanigai; Abdul Rahim, Hazli Rafis; Adnan Zain, Huda; Harun, Sulaiman Wadi (International Hellenic University, School of Science, 2022)
The development of reliable, lightweight, and effective sensors is a vital step in effectively monitoring critical parameter changes. This review focuses on the utilization of tapered optical fiber as a material sensing platform. The fundamental concept of the tapered fiber sensor is based on the interaction of strong evanescent waves caused by the fiber's dimensional change. The primary goal of this review is to explore the potential of tapered optical fiber for biosensing applications. A number of tapered optical fiber configurations and operations have been reviewed in order to propose appropriate optical sensor designs for biosensing applications. Hence, this analysis could serve as a benchmark for a more thorough study of biosensing device development.